Effects of Ba2+doping on microstructure and properties of PLMNT electro-optic ceramics fabricated by hot-pressed sintering process. Issue 23 (1st December 2022) - Jiang, Linjing; Cheng, Haijun; Sun, Dazhi; Zeng, Xia; Ling, Liang; Qiu, Pingsun; He, Xiyun
Abstract: A series of highly transparent electro-optic (EO) ceramics Pb0.975-x Bax La0.025 (Mg1/4 Nb1/2 Ti1/4 )0.99375 O3 with the Ba 2+ content of 0, 0.005, 0.01, 0.02, 0.04 were fabricated through the vacuum/oxygen hot-press sintering process. The effects of the barium substitution on the material phase transition, transmittance, dielectric, ferroelectric and electro-optic properties have been investigated and analyzed. With the Ba 2+ content increasing, the shape of the ferroelectric hysteresis loop changed from rectangular to slim, the values of remnant polarization (Pr ) and coercive electric field (Ec ) decreased obviously. The maximum reduction of Pr can reach up to ∼89.8%. All the samples present the high transparency of ∼68% in the near infrared wavelength. The quadratic EO coefficients declines slightly while the Ba 2+ content increasing. When the x is 0.01, the sample shows a relatively larger quadratic EO coefficient of ∼30.42 × 10 −16 (m/V) 2 and a lower Pr value of ∼2.08 μC/cm 2, which promise the material a hopeful application in EO modulator.